GAMBARAN KONSUMSI BUAH DAN SAYUR SERTA KONTRIBUSINYA TERHADAP KEBUTUHAN SERAT PADA NELAYAN DI PT. USAHA JAYA, PT. MAJU JAYA, PT. USAHA KERAMAT JAYA KOTA TANJUNGBALAI ASAHAN TAHUN 2012 - Suci Melfika; Evawany Y Aritonang; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Fruit and vegetable is one of the sources of the fiber consumed by fishermen. Consumption of fruit and vegetable by fishermen supplied  by company. PT. Usaha Jaya, PT. Maju Jaya and PT. Usaha Keramat Jaya are the company move in areas of fish catcher.This research is a descriptive study with cross-sectional design. The sample is  all population. The results of research show that type fruit in general consumed the fishermen at PT. Usaha Jaya and PT. Usaha Keramat Jaya  is papaya fruit (66,7% and 28,3%) while fishermen at PT. Maju Jaya is banana fruit (66,7%). And for type vegetables in general consumed the fishermen at PT. Usaha Jaya is cucumber, cabbage and pumpkin (33,3%) while fishermen at PT. Maju Jaya is eggplant (33,3%) and  fishermen at PT. Usaha Keramat Jaya is cabbage (50,0%).  Amount of fruit and vegetables consumption the fishermen at PT. Usaha Jaya, PT. Maju Jaya and PT. Usaha Keramat Jaya less than 300 gram and 200 gram  a day (100,0%). Frequency consumption of fruit and vegetables the fishermen at PT. Usaha Jaya 4-6 a week (100,0%), while fishermen at PT. Maju Jaya and PT. Usaha Keramat Jaya 1-3 a week. Average fiber consumption by fishermen at PT. Usaha Jaya, PT. Maju Jaya and PT. Usaha Keramat Jaya from fruit and vegetable  (2,9 gram, 3,0 gram and 3,1 gram) and for  average contribution of fruit and vegetable  fishermen at PT. Usaha Jaya, PT. Maju Jaya and PT. Usaha Keramat Jaya toward requirement fiber (7,57%, 8,1% and 8,4%).   Keywords : Fruit and Vegetable Consumption, Contribution of Fruit and Vegetable Fiber, Fishermen.